Effectiveness of Red Ginger (Zingiber officinale var. Rubrum) Foot Hydrotherapy in Lowering Blood Pressure among Pregnant Women with Hypertension - Soviyati, Evi; Utari, Toto Sutarto Gani; Fazrin, Risa Mustika (Universitas Islam Bandung, 2024)
Pregnancy hypertension is one of the complications of pregnancy. One nonpharmacological treatment to reduce hypertension is the foot hydrotherapy method with red ginger (Zingiber officinale var. rubrum). The essential oil content of red ginger provides a warm effect and spicy aroma so that blood vessels widen and blood flow becomes smooth. The research aims to determine the effectiveness of red ginger foot hydrotherapy in lowering blood pressure among pregnant women with hypertension. This one-group pretest-posttest pre-experimental study design was conducted at the Talaga Community Health Centre, West Java, from May 2023 to July 2023. The sample was 32 pregnant women with hypertension. Bivariate analysis test using paired t-test. The average systolic blood pressure measurement results for pregnant women before the intervention were 154.09 mmHg, and after the intervention was given 140.22 mmHg, there was a decrease of 13.87 mmHg. The average diastole for pregnant women before the intervention was 100.22; after the intervention, it was 91.62, resulting in a reduction of around 8.6 mmHg. The paired t-test with a p-value <0.001 shows the effectiveness of foot hydrotherapy with red ginger in reducing blood pressure in pregnant women with hypertension. Red ginger using the foot hydrotherapy method has been proven effective in lowering blood pressure in pregnant women. To reduce the risk factors for pregnancy with hypertension, pharmacological and nonpharmacological therapy is a solution that needs to be considered. This research can become a reference for evidence-based midwifery practice in providing midwifery care.